Impact of rosiglitazone on body composition, hepatic fat, fatty acids, adipokines and glucose in persons with impaired fasting glucose or impaired glucose tolerance: a sub‐study of the DREAM trial. Issue 9 (19th June 2014) - Punthakee, Z.; Alméras, N.; Després, J.‐P.; Dagenais, G. R.; Anand, S. S.; Hunt, D. L.; Sharma, A. M.; Jung, H.; Yusuf, S.; Gerstein, H. C.
Abstract Aims Thiazolidinediones reduce ectopic fat, increase adiponectin and reduce inflammatory adipokines, fatty acids and glucose in people with Type 2 diabetes. We aimed to measure these effects in people with impaired fasting glucose and/or impaired glucose tolerance. Methods After approximately 3.5 years of exposure to rosiglitazone 8 mg (n = 88) or placebo (n = 102), 190 DREAM trial participants underwent abdominal computed tomography and dual‐energy X‐ray absorptiometry scans. Visceral and subcutaneous adipose tissue areas, estimated hepatic fat content, total fat and lean mass were calculated and changes in levels of fasting adipokines, free fatty acids, glucose and post‐load glucose were assessed. Results Compared with the placebo, participants on rosiglitazone had no difference in lean mass, had 4.1 kg more body fat (P < 0.0001) and 31 cm2 more subcutaneous abdominal adipose tissue area (P = 0.007). Only after adjusting for total fat, participants on rosiglitazone had 23 cm² less visceral adipose tissue area (P = 0.01) and an 0.08‐unit higher liver:spleen attenuation ratio (i.e. less hepatic fat; P = 0.02) than those on the placebo. Adiponectin increased by 15.0 μg/ml with rosiglitazone and by 0.4 μg/ml with placebo (P < 0.0001). Rosiglitazone's effect on fat distribution was not independent of changes in adiponectin. Rosiglitazone's effects on fasting (–0.36 mmol/l; P = 0.0004) and 2‐h post‐load glucose (–1.21 mmol/l; P = 0.0008) were not affected by adjustment for fat distribution or changes in adiponectin or free fatty acids. Conclusions In people with impaired fasting glucose/impaired glucose tolerance, rosiglitazone is associated with relatively less hepatic and visceral fat, increased subcutaneous fat and increased adiponectin levels. These effects do not appear to explain the glucose‐lowering effect of rosiglitazone.